The Da'wah of Nahdlatul Ulama and Muhammadiyah in Social Media of Facebook - Dadan Suherdiana; Enjang Muhaemin (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2018)
The high number of social media users in Indonesia raises opportunities for various parties to use it. Not only for business, politics and campaign, but also for Islamic purposes. The two largest Islamic organizations in Indonesia, Nahdlatul Ulama (NU) and Muhammadiyah, also use facebook social media as a medium of propaganda. The research aims to find out the propaganda of NU and Muhammadiyah on facebook social media, both related to the missionary strategy and related to the portrait of the second da'wah of the largest religious organization in Indonesia. This study uses a qualitative approach, with data collection techniques carried out by literature study and observing both da'wah on the Facebook network. The data used in this study is qualitative data which is based on literature review and analysis of the two media Facebook organizations. The research resulted in a conclusion that the NU and Muhammadiyah da'wah strategies on facebook social media generally still use a normative pattern. Da'wah messages have not been creatively packaged, and generally still lack innovation. Da'wah material is still struggling in the area of aqeedah, morals and muamalah. Current issues that require study and solutions from an Islamic perspective are still relatively limited. Tingginya pengguna media sosial di Indonesia memunculkan peluang berbagai pihak untuk memanfaatkannya. Bukan hanya untuk bisnis, politik, dan kampanye semata, tetapi juga untuk syiar Islam. Dua ormas Islam terbesar di Indonesia yaitu Nahdlatul Ulama (NU) dan Muhammadiyah, juga memanfaatkan media sosial facebook sebagai media dakwah. Penelitian bertujuan untuk mengetahui dakwah NU dan Muhammadiyah di media sosial facebook, baik terkait dengan strategi dakwah maupun terkait potret dakwah kedua organisasi keagamaan terbesar di Indonesia ini. Penelitian ini menggunakan pendekatan kualitatif, dengan teknik pengumpulan data dilakukan dengan studi pustaka dan melakukan pengamatan terhadap dakwah keduanya di jejaring facebook. Data yang digunakan pada penelitian ini merupakan data kualitatif yang berpijak dari kajian pustaka dan analisis terhadap media facebook kedua organisasi tersebut. Penelitian menghasilkan simpulan bahwa strategi dakwah NU dan Muhammadiyah di media sosial facebook umumnya masih mengguinakan pola normatif. Pesan-pesan dakwah belum dikemas secara kreatif, dan umumnya masih minim inovasi. Materi dakwah masih berkutat di wilayah akidah, akhlak dan muamalah. Isu-isu kekinian yang membutuhkan kajian dan solusi dari perspektif keislaman masih relatif terbatas.